Rwanda Investor Perceptions Survey 2018 - World Bank Group (World Bank, Washington, DC, 2018)
The Rwanda Investor Perceptions Survey is a publication of the World Bank Group and the Rwanda Development Board, in partnership with the United Kingdom’s Department for International Development. The survey, published in June 2018, identifies investor perceptions of Rwanda as an investment destination with a focus on export-oriented companies in the tea, horticulture, agro-processing, minerals, manufacturing, tourism, ICT, and healthcare sectors. The survey highlights opportunities in the Rwandan market and draws attention to areas for potential improvement of Rwanda as an investment destination.